The path from the choroid plexus to the subventricular zone: go with the flow! - Falcao, Ana M.; Marques, Fernanda; Novais, Ashley; Sousa, Nuno; Palha, Joana A.; Sousa, Joao C. (Frontiers in Cellular Neuroscience, 2012)
In adult mammals, under physiological conditions, neurogenesis, the process of generating new functional neurons from precursor cells, occurs mainly in two brain areas: the subgranular zone in the dentate gyrus of the hippocampus, and the subventricular zone (SVZ) lining the walls of the brain lateral ventricles. Taking into account the location of the SVZ and the cytoarchitecture of this periventricular neural progenitor cell niche, namely the fact that the slow dividing primary progenitor cells (type B cells) of the SVZ extend an apical primary cilium towards the brain ventricular space which is filled with cerebrospinal fluid (CSF), it becomes likely that the composition of the CSF can modulate both self-renewal, proliferation and differentiation of SVZ neural stem cells. The major site of CSF synthesis is the choroid plexus (CP); quite surprisingly, however, it is still largely unknown the contribution of molecules specifically secreted by the adult CP as modulators of the SVZ adult neurogenesis. This is even more relevant in light of recent evidence showing the ability of the CP to adapt its transcriptome and secretome to various physiologic and pathologic stimuli. By giving particular emphasizes to growth factors and axonal guidance molecules we will illustrate how CP-born molecules might play an important role in the SVZ niche cell population dynamics.